A Descriptive Analysis of the Interactions During Clinical Supervision - Novoa-Gómez, Mónica; Córdoba-Salgado, Oscar; Rojas, Natalia; Sosa, Luis; Cifuentes, David; Robayo, Sara (Frontiers in Psychology, 2019)
This study analyzes the different kind of skills trained during supervision by describing the set of responses (based on the APA, 2006; competency domains) occurring between the supervisor and the supervisee during the supervision process, aimed at the supervisee’s skill development. Interactions from twelve supervisor-supervisee dyads during asynchronous and direct, and individual and group supervision sessions were video recorded for this purpose. The recordings served to determine, classify, and define behavioral response classes in each dyad’s interactions. Percentages of time spent in each behavior class was computed. A reliability of 95% CI [.91, 0.95] between observers was obtained. The behavior classes in which more time was spent were assessment, intervention and conceptualization skills. Behavior classes in which less time was spent were related to emotional and interpersonal processes. These findings are discussed by linking the evidence-based theory on supervision with the time spent in each behavior class.